A extensão ub−l(1) do modelo padrão - Freitas, Felipe Ferreira de (2013)
The fact that neutrinos are massive indicates that the Standard Model (MP) should be extended. In this thesis we study the gauge extension called B-L, which is based on the symmetry group SUci (3) SUL (2) Uy (1) UB_L(l). The additional factor UB_L(l) brings up a new boson, called Z ', then the addition of a new scalar is needed to break this new symmetry. We will show that this model provides a natural background for right-handed neutrinos and the see-saw mechanism of mass production. Moreover, we find some phenomenological aspects of this model, as the absence of anomalies and some decay widths of the new boson. Finally, a brief analysis is made of how this new boson can be produced in acleradores particle and its lower bounds of his mass.